Inovasi Pelayanan Pembayaran Pajak Kendaraan Bermotor Melalui Program Pelayanan SAMSAT Virtu - Selvi Tamia; Rosidi Rosidi; Titi Darmi (JOPPAS: Journal of Public Policy and Administration Silampari, 2022)
The purpose of the study was to describe the service of paying motorized vehicle taxes and to find out the obstacles in the service of paying motorized vehicle taxes at SAMSAT Virtu Bengkulu. The method used in this study is a qualitative descriptive method. The results of the study found that the motor vehicle tax payment service at SAMSAT Virtu Bengkulu has provided the best service to taxpayers easily, quickly, and accurately so that tax revenues are still obtained to the maximum. This can be seen from five indicators, namely: Tangible (physical evidence), Reliability (reliability), Responsiveness (capability), Assurance (guarantee), and Empathy (comfort). The conclusion of this research is that the motor vehicle tax payment service through the SAMSAT Virtu Bengkulu program has been going well. Keywords: Motor Vehicle Tax, Public Service, SAMSAT Virtu